Effects of Astragalus Extract Mixture HT042 on Circulating IGF-1 Level and Growth Hormone Axis in Rats - Donghun Lee; Byung-Hak Kim; Sung-Hyun Lee; Won-Young Cho; Young-Sik Kim; Hocheol Kim (MDPI AG, 2021)
Astragalus extract mixture HT042 is a standardized functional food granted by the Korean FDA for promoting "Children's Height Growth". In this study, we determined whether HT042 affects circulatory Insulin-like growth factor-1 (IGF-1) after administration and investigated whether Growth hormone (GH), Growth hormone-releasing hormone receptor (GHRH-R), and Growth hormone secretagogue receptor (GHS-R) mRNAs are expressed in the pituitary, and whether Growth hormone-releasing hormone (GHRH) and Somatostatin (SST) are expressed in the hypothalamus. We also evaluated the growth effect of HT042 on endochondral bone formation. Male Sprague-Dawley rats in the control and HT042 groups were orally administered a single dose of the control and HT042, respectively, and those in the recombinant human GH (rhGH) group were subcutaneously injected with rhGH. Tetracycline was injected intraperitoneally 72 h prior to sacrifice to decide endochondral bone formation. To determine the endocrine or paracrine/autocrine mechanism, we evaluated the expression of local BMP-2 and IGF-1, an immunohistochemical study after HT042 administration. It was confirmed that the growth-promoting effect of HT042 can be contributed to the increase in serum IGF-1, which can be stimulated by GH secretion. Administration of HT042 modulated the activity of GHRH-R and GHR-S in the pituitary gland and promoted GH secretion, thereby changing longitudinal growth through GH/IGF-1 mediation. Results for GHRH and SST expression demonstrated that the hypothalamus can be influenced and mediated by HT042 through a complex neuroendocrine regulatory system. In addition, it was confirmed by oral administration for 10 days that HT042 increased bone formation in cartilage, which is important for height growth. The effect of HT042 could be owing to upregulation of local Bone morphogenetic protein-2 (BMP-2) and IGF-1 expression in the growth plate, which could be regarded as a GH-dependent autocrine/paracrine pathway, as well as circulatory IGF-1.